The Possible Impact of Hosting a Cultural Event on Destination Image: A case study -- Liverpool as a host city for 2008 European Capital of Culture - Wu, ZhiYong (2007)
Destination image is commonly accepted as an important aspect in successful tourism development and destination marketing. Faced with growing global competition in which destinations are becoming highly substitutable, destination marketing organizations are in a constant battle to attract travellers (Pike and Ryan, 2004). Among different strategies, employing events has been seen as a successful way to strengthen, enhance or change a destination image.